Study on the relationship between radon characteristics of underground water and seismicity in the Longxian - Baoji fault zone, NW China. Issue 1 (September 2020) - Liu, Jie; Zhao, Xiaomao; Wang, Xin; Wang, Jingli; Qiu, Yurong
Abstract: Destructive earthquakes are mostly located in the active fault zones. The underground gas anomalies result to basically be consistent with the inferred distribution of active fault systems. Among them, radon is the earliest used as the effective prediction index of fault zone earthquake prediction. In this paper, radon concentrations in groundwater from the Longxian – Baoji fault zone in the Northwestern China are analyzed. Results show that the NW sector has a lower radon concentration (∼12 Bq/L) than that of the SE sector (40 ∼ 50 Bq/L). It indicated that the connectivity between the shallow and deep crust is relatively poor in the NW sector, which is not conducive to the upward diffusion and migration of deep fluids. Given that there is a seismic gap with no rupture of M ≥ 6 1/2 strong earthquake in the NW sector, it can be infered that the NW sector of the Longxian - Baoji fault zone has a higher risk of strong earthquakes than that in the SE sector.